THE EFFECT OF SCAFFOLDING IN STORY REENACTMENT ON JUNIOR HIGH SCHOOL EFL STUDENTS’ SPEAKING SKILLS - Betsi Daputri Rahayu; Agus Sholeh; Rizky Lutviana (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Junior high school students in EFL contexts frequently encounter challenges in speaking. These challenges are not primarily caused by insufficient language knowledge, but rather by limited opportunities to use English during communicative classroom activities. Another factor that contributes to students speaking difficulties is high speaking anxiety. This study aimed to examine the effect of scaffolding in story reenactment activities on junior high school students’ speaking skills in EFL contexts. The study employed a quasi-experimental method with a pretest-posttest control group design involving two eighth grade classes at SMPN 23 Malang. The sample consisted of 54 students who were assigned into an experimental group (n=26) and a control group (n = 28). The data collection process used speaking tests using an analytic scoring rubric covering fluency, grammatical accuracy, vocabulary, pronunciation, and content. The findings showed that the experimental group achieved greater improvement than the control group across all speaking components, particularly grammatical accuracy and fluency. The result of The Mann-Whitney U test showed that the two groups were significantly different (p = .002) with an effect size of .42. The findings indicate that the implementation of scaffolding in story reenactment helped students manage linguistic and cognitive demands during oral production, thereby supporting better speaking performance in junior high school EFL classrooms. ABSTRAK Siswa SMP dalam konteks belajar bahasa inggris sebagai bahasa asing (EFL) kerap menghadapi kesulitan dalam berbicara (speaking). Hal ini terjadi bukan karena kurangnya pengatuhan bahasa yang mereka miliki, melainkan karena minimnya ksesempatan berlatih secara komunikatif di dalam kelas. Kesulitan tersebut juga terjadi karena tingginya kecemasan saat berbicara serta aktitifitas pembelajaran. Penelitian ini bertujuan untuk menganalisis pengaruh scaffolding dalam kegiatan story reenactment terhadap kemampuan berbicara siswa SMP dalam konteks EFL. Penelitian ini menggunakan desain kuasi-eksperimen dengan metode pretest-posttest yang melibatkan dua kelas VIII di SMPN 23 Malang. Sample berjumlah 54 siswa yang dibagi ke dalam kelompok eksperimen (n=26) dan kelompok kontrol (n=28). Data penelitian diperoleh melalui tes kemampuan berbicara menggunakan rubrik analitik yang mencakup fluency, gramatical accuracy, vocabulary, pronunciation, dan content. Hasil menunjukkan bahwa kelompok eksperimen mengalami peningkatan kemampuan berbicara yang lebih tinggi dibandingkan dengan kelompok kontrol pada seluruh komponen berbicara, terutama gramatical accuracy dan fluency. Hasil uji Mann-Whitney U menunjukkan adanya perbedaan signifikan antara kedua kelompok (p = .002) dengan effect size sebesar .42. Temuan penelitian menunjukkan bahwa penerapan scaffolding dalam story reenactment membantu siswa mengurangi beban linguistik dan kognitif selama proses produksi lisan sehingga mendukung performa berbicara yang lebih baik dalam pembelajaran EFL tingkat SMP.